The effect of dance therapy on the balance of women over 60 years of age: The influence of dance therapy for the elderly. (4th July 2017) - Filar-Mierzwa, Katarzyna; Długosz, Małgorzata; Marchewka, Anna; Dąbrowski, Zbigniew; Poznańska, Anna
ABSTRACT: Dance therapy is a physical activity that can lead to balance improvement in older adults. The aim of the study was to evaluate the effects of dance therapy on balance and risk of falls in older women. Twenty-four older women (mean age 66.4 years old) attended dance sessions for three months. Pretest/posttests were completed using the Postural Stability Test, the Limits of Stability Test, and the Fall Risk Test M-CTSIB. Results showed the Limits of Stability Test was significantly higher (17.5%) after dance classes. Regular use of dance therapy shows promise in improving balance by increasing the limits of stability.